A New Museum Typology?: The Depot Boijmans Van Beuningen in Rotterdam. Issue 1 (2nd January 2021) - Kisters, Sandra
Abstract: The focus of this paper and case study is the public art Depot Boijmans Van Beuningen, which will open in 2021 in Rotterdam. In our marketing campaign we present the Depot as the first fully public art storage facility in the world; but in fact,  the development of opening up collections to the general public has been a focus for many institutions in the last decade. The concept of the Depot Boijmans Van Beuningen relates to different strategies for making the collection accessible, from visible storage and visitable storage, to the older concept of collection study rooms and the presentations we intend to make in the two public galleries within the depot, on the topics of collection care and collecting. With the opening of this building, we aim to reach a wider audience than the one that normally visits the museum, whom we will address as fellow collectors and owners of this public collection. While there are notable tensions between the public function of the building and the museum's primary vocation to preserve the collection for future generations, this new space also has the advantage of placing ignored artworks in the spotlight. The Depot Boijmans Van Beuningen represents a new typology in the museum field, in particular in the visual arts; however, there are more initiatives on the way,  including the V&A East in London or the Centre Pompidou's new collection centre in the suburbs of Paris. A collection centre open to the public is not a feasible model for every museum, particularly because it is expensive and makes strong demands on organisations. In the future, we will face questions around unlimited collection growth and de-accessioning. Nonetheless, the Depot Boijmans Van Beuningen represents an effort to keep the depository active and more accessible.